The Influence of Customer Satisfaction, Customer Experience, and Customer Loyalty toward Brand Power in the Case of Spotify - Jenifer Jenifer; Felicia Dea (iBuss Management, 2023)
Spotify is currently the world’s most famous online streaming music platform in the world. However, it does not guarantee the brand to be famous in each country. Spotify needs to face the hard reality of the platform losing to JOOX in the Indonesian market. As customers play a vital role in the company’s success in the market, Spotify needs to understand its customers due to its effect on its revenue. This will result in the customer feeling appreciated since they can feel the best experience which will lead to the likelihood of renewing the subscription to the service and improve the brand in the market. Hence, the researchers are captivated in helping Spotify to be the market leader in Indonesia by analyzing the relationship between the customer experience, customer satisfaction, and customer loyalty towards its brand power. This research uses a quantitative approach where the researchers use probability sampling design, especially the simple random sampling method and the selected population is Indonesian people who have used Spotify Indonesia, have known about Spotify's promotion in Indonesia and with the age of above 17 years old with a sample size of 76. The data from 76 respondents were analyzed using PLS-SEM through SmartPLS 4 to examine the results of the outer and inner models. The finding shows that  customer experience, customer satisfaction, and customer loyalty had significant positive effects toward brand power in the case of Spotify.Keywords: brand power, customer loyalty, customer satisfaction, customer experience, Spotify.